(untitled) (Journal of the College of Basic Education, 2023)
Abstract This study is divided into two sections and a conclusion. Section one is an introduction and critical reception, while section two talks about MacNeice’s poems and the irony in his poetry. Irony in MacNeice’s poetry seeks to present his perception of the world around his perception of the world around him.And while MacNeice does not seek to hide the sorrow, he attempts to display this sorrow with a touch of light heartedness. As Louis MacNeice illustrates, even death and despair can have a lighter side. The conclusion sums the main findings of the study. MacNeice is a slight bit impersonal at times, but only insofar as he does not explicitly place himself as the speaker by using me. Just as he looks at life’s flax in. Variations on Heraclitus, his take on the Greek philosopher Heraclitus’ idea that one can never step in the same river twice due to the constant movement of the world around us. MacNeice’s notion is that one is not to be apprehensive about these uncertainties but simply to take them as they come. MacNeice takes on the issue of licentiousness and promiscuity and while poking fun he exposes the lonely and decrepit final condition of the libertine. In this manner, and even if MacNeice was not personally a libertine, we can be sure that this is an issue he thought about. Otherwise, thus MacNeice achieves both arm’s length discussion of a social issue and an ironic look at a playboy who is representative of many a poet. the poet does not give you a full and accurate picture of the world nor a full and accurate picture of himself, but he gives an amalgam which, if successful, represent truthfully his own relation to the world. Thus the modern poetry of MacNeice does not simply speak of abstract social issue such as sexual licentiousness or if strictly personal issues. His modern poetry is blend of personal emotion and social issues, personal not in a heavy - handed tone but with satire and irony. For in the real world, sorrow exists side by side with joy and laughter.